Cardiac capillary hemangioma: A case report and brief review of the literature. Issue 1 (17th January 2013) - Han, Yuna; Chen, Xin; Wang, Xiaobing; Yang, Liang; Zeng, Yanling; Yang, Jun
<x xml:space="preserve">Abstract</x> Among primary cardiac tumors, hemangiomas are relatively rare, with a reported incidence of 2.8%. To date, less than 100 cases have been reported in literature. We report the case of a 61‐year‐old woman who complained from chest discomfort since 3 years and in whom transthoracic echocardiography revealed a pedunculated tumor in the left ventricle. The tumor was successfully resected and its histopathological examination revealed a capillary hemangioma. The patient had an uneventful recovery without any complication. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound 42:53–56, 2014